Crosstalk between Brassinosteroids and Ethylene during Plant Growth and under Abiotic Stress Conditions - Jiroutova, Petra; Oklestkova, Jana; Strnad, Miroslav (International journal of molecular sciences, 2018)
Plant hormones through signaling networks mutually regulate several signaling and metabolic systems essential for both plant development and plant responses to different environmental stresses. Extensive research has enabled the main effects of all known phytohormones classes to be identified. Therefore, it is now possible to investigate the interesting topic of plant hormonal crosstalk more fully. In this review, we focus on the role of brassinosteroids and ethylene during plant growth and development especially flowering, ripening of fruits, apical hook development, and root and shoot growth. As well as it summarizes their interaction during various abiotic stress conditions.
Keywords: ethyleny; Ethylenes; Signal Transduction; ethylene; stress tolerance; signální transdukce; plant growth; vývoj rostlin; Plant Development; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; brassinosteroid; brassinosteroidy; Brassinosteroids